God in the courtroom religion's role at trial - Bornstein, Brian H.; Miller, Monica K. (New York ; Oxford : Oxford University Press, 2009)
The authors review legal developments and behavioural science research concerning the effects of religion on legal practice decision-making processes of various actors and trial outcomes. Chapters address jury selection and bias, attorneys' use of religion in legal movements, judges' religious belief, and much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Justice, Administration of -- United States -- Psychological aspects; Judicial process -- United States -- Psychological aspects; Religion and law -- United States; Judges -- United States; Jury -- United States